ANALISIS KADAR SERAT PADA SNACK BAR DENGAN BERBAGAI KOMPOSISI TEPUNG BERAS HITAM (ORYZA SATIVA L) DAN TEPUNG KACANG MERAH (PHASEOLUS VULGARIS L) - Fitriana, Dwi Indah Nur; Setiadi, Yuwono (Poltekkes Kemenkes Semarang, 2017)
Background: the Level of fiber consumption of Indonesia's population in general is still low, so the need for innovation in product development of prepared foods that are high in fiber. Examples of materials that can be used can be used is black rice and red beans that have fiber content to 28.59 g% 35,44% g and allows to be added in the manufacture of snack bar. Objective: to determine the effect of various differences in the composition of rice flour and black bean flour red against the fiber content and the received power snack bar. Method: 1 factors, i.e. differences in the composition of rice flour and black bean flour red as well as 5 standard of treatment, i.e. the composition of A, B, C, D, and E and 3 times repetition. Fiber content was analyzed by using gravimetric method. Received power carried out by 20 panelists using hedonic test. Results: No influence of differences in the composition of rice flour and black bean flour red against the fiber content the snack bar (p= 0.016; p0,01). There is the influence of differences in the composition of rice flour and black bean flour red against the received power of the texture on the composition of A with D (p= 0.007) as well as a sense between the composition of B with D (p= 0.003) and B with E (p= 0.001) and no effect on the color and aroma of the snack bar. Conclusion: the Composition of the snack bar which is recommended to be developed is the composition C (50% rice flour and black bean flour red) with the donation of the fiber by 21,24 g%.